Pemberdayaan Ekonomi Lansia Dengan Pelatihan Pembuatan Minuman Herbal (Wedang Empon-Empon) Dalam Kemasan Sachet - Surahman, Sukma Hendra Wahyudi; Suseno, Aji (PT. Kreasi Karya Majakata, 2025)
The Community Service Program (PkM) is an effort to realize service aimed at improving the lives of the community. In this PkM activity, the aim is to empower the elderly through training in the production of herbal powder drinks in sachet packaging as a form of creativity and an effort to improve family economics. The activity was conducted at the BPW Kras Adult Sunday School in Kediri, with the main targets being the elderly and productive adults. The training includes socialization of the benefits of herbal ingredients such as ginger, turmeric, temulawak, and kencur, as well as practical sessions on making and packaging herbal products. The methods used were demonstrations, hands-on practice, and participatory evaluation. The results show an increase in participants' knowledge and skills in recognizing herbal ingredients and producing health drinks. This program shows that the elderly have the potential to actively contribute to productive activities if provided with appropriate training and support for their needs.